CONVERSION OF TANAH SANGKOL AND ENVIRONMENTAL DAMAGE IN SUMENEP REGENCY - A Zahid; Muhammad Khoirul Malik; Jariah Sinta Ayni (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study aims to analyse the impact of tanah sangkol conversion on environmental damage in Sumenep Regency, Madura, and to understand the social factors that influence changes in land function. Tanah Sangkol conversion, generally in the form of conversion of agricultural land to land for settlements or the shrimp farming industry, is an important issue that impacts environmental quality and community welfare. This research methodology uses a qualitative approach with data collection techniques through in-depth interviews and participatory observation. The study results indicate that tanah sangkol conversion in Sumenep has caused soil quality degradation, reduced productive agricultural areas, and decreased biodiversity. Social factors influencing land conversion include increased demand for residential and industrial land, economic pressures, and weak implementation of environmental protection policies. In addition, uncertainty in land use regulations has worsened environmental conditions in the Sumenep area. The contribution of this study to sociology is to provide an understanding of the relationship between social, economic, and environmental dynamics in the context of land conversion. This study also contributes to the study of social change related to natural resource management and its impacts on local communities, especially in efforts to achieve sustainable development. Thus, this research can be a reference for more holistic land and environmental management policies in rural areas.